TERAPÖTİK ABORTUS - AKSU, M. Feridun; ORAL, Engin; YEDİGÖZ, Veli; ATASÜ, Turgay; KAZANCIGİL, Aykut (Cerrahpaşa Medical Journal, 2014)
Background and Design. Therapeutic abortion and its problems has always been of considerable interest to both the medical and legal societies. Women who have major medical disorders, have fetuses with major malformations and chromosomal abnormalities are eligible for pregnancy termination. Therapeutic abortion was approved in 1967 in Republic of Turkey. In our study, one hundred twenty nine medical abortions performed in our clinic between 1982 1996 years were reviewed. Their clinical features, indications, and techniques are discussed. The data compared with the 30 years cumulative data of our clinic. Results. During this period (19821996) there were 129 therapeutic abortions carried out in our institute. The ratio of therapeutic abortions to deliveries was 1:514. There were 55 (%42.6) primigravidas in the series. Fetal indications were more frequent (85 cases, 65.9%) than maternal ones (44 cases, 34.1 %). In 112 of 129 (87%) abortion occurred before 25 weeks. Neural tube defects and multiple congenital anomalies were the main causes of fetal indications (36.4%), whereas heart disease was the most common cause of maternal indications (13.2). Medical methods were used more frequent than surgical methods for the termination of pregnancy (65.3% vs 34.7%). Conclusion. Because of the enhanced care of the pregnant women; nowadays fetal indications for therapeutic abortions outnumber maternal ones and medical methods are preferred most of the time for these procedures.